Effect of low-level laser therapy on the healing process after tooth replantation: a histomorphometrical and immunohistochemical analysis - Matida Hamata Saito, Celia Tomiko [UNESP]; Gulinelli, Jessica Lemos [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Garcia, Valdir Gouveia [UNESP]; Okamoto, Roberta [UNESP]; Okamoto, Tetuo [UNESP]; Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2011)
Success of tooth replantation is limited because part of the replanted tooth is lost because of progressive root resorption. This study used histomorphometry and immunohistochemistry to evaluate the effect of low-level laser therapy (LLLT) on the healing process of rat teeth replanted after different extra-oral periods, simulating immediate and delayed replantation. Sixty Wistar rats (Rattus norvegicus albinus) had their maxillary right incisors extracted and randomly assigned to six groups (n = 10): C4, C30 and C45, in which the teeth were replanted 4 min (immediate), 30 min (delayed) and 45 min (delayed) after extraction, respectively, and L4, L30 and L45, in which the teeth were replanted after the same extra-alveolar times, but the root surfaces and the alveolar wounds were irradiated with a gallium-aluminum-arsenate (GaAlAs) diode laser before replantation. The animals were sacrificed after 60 days. The anatomic pieces containing the replanted teeth were obtained and processed for either histomorphometrical analysis under optical microscopy or immunohistochemical expression of receptor activator of nuclear factor Kappa-B (RANK), and its ligand (RANKL), osteoprotegerin (OPG) and tartrate-resistant acid phosphatase (TRAP) proteins. Areas of external replacement and inflammatory root resorption were observed in all groups, without statistically significant differences (P > 0.05). Ankylosis was more frequent in L30 than in C30 (P < 0.05). RANKL immunostaining predominated over RANK and OPG immunostaining in both groups with immediate tooth replantation (P < 0.05). For the 45-min extra-alveolar time, however, there was greater evidence of RANK immunostaining compared to RANKL for both control and laser-treated groups (P < 0.05). Positive TRAP immunostaining predominated in L4 and L30 (P < 0.05). In conclusion, under the tested conditions, the treatment of the root surface and the alveolar wound with LLLT did not improve the healing process after immediate and delayed tooth replantation in rats.